Current transformer reaction with total harmonic distortion - Khairul Anuar, Mohd Nor; Ismail, Daut, Prof. Dr.; Indra, Nisja; M., Reza; Nor Ashbahani, Mohamad Kajaan (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.